Study of morphological traits changes in different media culture of two apple rootstocks (M26 and MM106) - Noormohammadi, Z.; Farahani, F.; Safarzadeh, M. (Penerbit Universiti Kebangsaan Malaysia, 2013)
Numerous studies have reported on regeneration from apple somatic tissues, andorganogenesis has been proved to be influenced by several factors including mother shoots (genotype, size, type, and age of explant), in vitro conditions (dark period, light intensity, and quality), and others (wounding, orientation of leaf explants). However, one of the most important factors during the regeneration process ismicro and macro elements in media culture and the type and concentration of cytokinin applied. For optimization of the elongation shoot and proliferation medium, two different macro and micro element formulations were tested: MS and DKW. The 2-isopentnyl adenine (2-ip) and benzyl adenine (BA) are the most frequently used cytokinins in the regeneration systems, but their efficiency depends on genotype and other factors. The organogenic ability of explants can also be increased by a properly selected cytokinin treatment. Phytohormones (2 mgl-1 BA and 2 mgl-1 2-ip with 0.1 mgl-1 IBA) established for the proliferation of M26 and MM106 apple rootstocks. The both of rootstocks, the MS medium with BA (2 mgl-1) yielded in general the best shoot growth and elongation of branch also, DKW with 2-ip (2 mgl-1) showed the best callus formation and branching. Significantly better growth with the MS medium was also favored by BA as the cytokinin.